Childhood maltreatment as a risk factor for COPD: findings from a population-based survey of Canadian adults - Shields, Margot E (Int J Chron Obstruct Pulmon Dis, 2016)
OBJECTIVE: The aim of this study was to examine the associations between childhood maltreatment (CM) and COPD in adulthood. METHODS: Data were from 15,902 respondents to the 2012 Canadian Community Health Survey – Mental Health. Multiple logistic regression models were used to examine associations between CM and COPD and the role of smoking and mental and substance use variables as mediators in associations. RESULTS: COPD in adulthood was related to CM, with associations differing by sex. Among females, COPD was related to childhood physical abuse (CPA), childhood sexual abuse, and childhood exposure to intimate partner violence, but in the fully adjusted models, the association with CPA did not persist. Among males, COPD was related to childhood exposure to intimate partner violence and severe and frequent CPA, but these associations did not persist in the fully adjusted models. CONCLUSION: Results from this study establish CM as a risk factor for COPD in adulthood. A large part of the association is attributable to cigarette smoking, particularly for males. These findings underscore the importance of interventions to prevent CM as well as programs to assist victims of CM in dealing with tobacco addiction.